Noncommunicable disease incidences in 2012-2017, Turkey. (20th October 2021) - Ergor, G; Sakarya, S; Sozmen, K; Dinc Horasan, G; Ekinci, B; Arıkan, A; Sis, S; Unal, B
Abstract: Background: Globally, 88% of deaths are caused by noncommunicable diseases (NCD) and they are increasing in our country as in many parts of the world. Effective control, prevention and treatment of NCD, can begin from knowing the disease incidence by age, sex and regions. Methods: This study aimed to determine the incidence of chronic diseases (coronary heart disease, stroke, diabetes, hypertension and cancer) by record linkage of the data from the Turkey Chronic Diseases and Risk Factors Prevalence Study 2011 (TCD-RFS) with health service databases, which are Family Medicine Information System, Medulla- E-Pulse and Death Notification System. The cohort (18.477 people above age 15) from TCD-RFS is followed up to determine the incidence of coronary heart disease, hypertension, diabetes, stroke and cancer, from the electronic health record systems for the period between 2012 and 2017 (6 years). Cumulative incidences were calculated, age and sex standardized incidences were given with 95% CI. Results: The age and sex standardized cumulative incidences are, 5939 (95% CI 5933-5945) for CHD 1378 (95%CI:1369-1388) for stroke, 2254 (95% CI 2 253 -2 255) for cancer, 4200 (95% CI 4194-4204) for diabetes and 20788 (95% CI 1369-1388) for hypertension (per 100, 000). The annual incidences are approximately 990 for CHD, 229 for stroke, 375 for cancer, 700 for diabetes and 3464 for hypertension (per 100, 000). CHD and cancer incidences are higher in men, while diabetes, hypertension and stroke incidences are higher in women. Conclusions: Regardless of the difficulties in comparing incidence of NCD with other countries, we think our results show that hypertension, diabetes, stroke and CHD have higher incidence than Western European countries. We also showed that these metrics can be obtained through data linkage of National Health Records for the first time in Turkey. Key messages: The NCDs needs to be monitored by surveillance using the current data sources for health services. This data can provide very useful information regularly to monitor and control NCDs if necessary actions are taken to adjust data management.